Ecological drivers of global gradients in avian dispersal inferred from wing morphology - Catherine Sheard; Montague H. C. Neate-Clegg; Nico Alioravainen; Samuel E. I. Jones; Claire Vincent; Hannah E. A. MacGregor; Tom P. Bregman; Santiago Claramunt; Joseph A. Tobias (Nature Communications, 2020)
In birds, the hand-wing index is a morphological trait that can be used as a proxy for flight efficiency. Here the authors examine variation of hand-wing index in over 10,000 bird species, finding that it is higher in migratory and non-territorial species, and lower in the tropics.